Predicting consumers' choices in the age of the internet, AI, and almost perfect tracking: Some things change, the key challenges do not. Issue 1 (9th December 2020) - Gal, David; Simonson, Itamar
Abstract: Recent technology advances (e.g., tracking and "AI") have led to claims and concerns regarding the ability of marketers to anticipate and predict consumer preferences with great accuracy. Here, we consider the capabilities of both traditional techniques (e.g., conjoint analysis) and more recent tools (e.g., advanced machine learning methods) for predicting consumer choices. Our main conclusion is that for most of the more interesting consumer decisions, those that are "new" and non‐habitual, prediction remains hard. In fact, in many cases, prediction has become harder due to the increasing influence of just‐in‐time information (user reviews, online recommendations, new options, etc.) at the point of decision that can neither be measured nor anticipated ex ante. Sophisticated methods and "big data" can in certain contexts improve predictions, but usually only slightly, and prediction remains very imprecise—so much so that it is often a waste of effort. We suggest marketers focus less on trying to predict consumer choices with great accuracy and more on how the information environment affects the choice of their products. We also discuss implications for consumers and policymakers.